2021
DOI: 10.1371/journal.pone.0258789
|View full text |Cite
|
Sign up to set email alerts
|

Association between nitric oxide synthase T-786C genetic polymorphism and chronic kidney disease: Meta-analysis incorporating trial sequential analysis

Abstract: Background Several meta-analyses of the relationship between endothelial nitric oxide synthase (eNOS) T-786C gene polymorphism and chronic kidney disease (CKD) have been published. However, the results of these studies were inconsistent, and it is undetermined whether sample sizes are sufficient to reach a definite conclusion. Objective To elucidate the relationship between T-786C and CKD by combining previous studies with our case-control sample and incorporate trial sequential analysis (TSA) to verify whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…( 1) Toll-like receptor (TLR) gene mutations have been linked with the development of kidney disease, 24 (2) Angiotensin-converting enzyme (ACE) insertion-deletion polymorphism has also been linked with the development of diabetic nephropathy 25 (3) Another study looked for endothelial nitric oxide synthase gene (G894T, 4b/a, and T786C) polymorphism and development of diabetic nephropathy. 26 Genes, for example, that for catalase, related to oxidative stress are associated with diabetes and nephropathy independently. 27 A recent study has reported the involvement of pro-inflammatory cytokines interleukin-16 and interleukin-18 gene expression with the development of diabetic nephropathy but it does not comment on the severity or early onset of disease.…”
Section: Discussionmentioning
confidence: 99%
“…( 1) Toll-like receptor (TLR) gene mutations have been linked with the development of kidney disease, 24 (2) Angiotensin-converting enzyme (ACE) insertion-deletion polymorphism has also been linked with the development of diabetic nephropathy 25 (3) Another study looked for endothelial nitric oxide synthase gene (G894T, 4b/a, and T786C) polymorphism and development of diabetic nephropathy. 26 Genes, for example, that for catalase, related to oxidative stress are associated with diabetes and nephropathy independently. 27 A recent study has reported the involvement of pro-inflammatory cytokines interleukin-16 and interleukin-18 gene expression with the development of diabetic nephropathy but it does not comment on the severity or early onset of disease.…”
Section: Discussionmentioning
confidence: 99%